Effect of TiO2 and TiN on the Viscosity, Fluidity, and Crystallization of Fluorine‐Free Mold Fluxes for Casting Ti‐Bearing Steels. Issue 2 (11th September 2020) - Wang, Wanlin; Cai, Dexiang; Zhang, Lei; Sohn, Il
Abstract : TiN inclusions are known to exacerbate slag rimming and nozzle clogging during continuous casting of Ti‐bearing steels. Herein, the effect of TiO2 and TiN on the viscosity and fluidity of a fluorine‐free (F‐free) mold flux, as well as the corresponding precipitated crystalline phase is studied. Higher TiO2 is found to lower the viscosity and increase the strip length of the molten slag at TiO2 contents less than 10 wt%, whereas the viscosity increases suddenly and the strip length decreases rapidly at TiO2 contents above 10 wt%, due to the precipitation of CaTiO3 crystals, resulting in a solid–liquid coexisting melt. TiN has a low solubility in F‐free mold fluxes without MnO additions, and TiN is distributed in the molten slag as solid particles. TiN addition significantly increases the viscosity and shortens the strip length of the molten slag. On the other hand, F‐free mold fluxes containing MnO dissolves TiN into the molten slag through the oxidization of TiN to TiO2 . However, beyond the solubility limit of TiN in fluorine‐free mold fluxes containing 5 wt% MnO, excess TiN is not completely dissolved. Then, the precipitation of Ca2 Ti2 O6 crystals is promoted. Abstract : TiN inclusions are dissolved effectively by MnO in mold fluxes; then, the rheological behavior of molten slag is not deteriorated. But the excessive TiN is not dissolved completely and promotes the precipitation of Ca2 Ti2 O6 crystals, leading to the viscosity increase and the fluidity reduction of slag. So, molten steel cleanliness should be ensured during the steelmaking process.